Konsep Dasar Strategi Pembelajaran Aktif dan Implementasinya dalam Pembelajaran Pendidikan Agama Islam - Ira Kurnia Putri; Famela Annisa Ziqri; Gusmaneli Gusmaneli (Politeknik Kampar, 2024)
Currently, Islamic education is still faced with unpleasant internal criticism. One such criticism is that Islamic education is taught more through rote memorization than practice, even though Islam has many values to be applied. Learning that is based on the wishes of the teacher and does not pay attention to the individual differences of children will be difficult to encourage students to achieve learning goals. Research is carried out using literature methods, or literature studies, which involve collecting data from various sources available online, such as books, scientific journals, theses, and others. Active learning is defined as an approach in which students are actively engaged in their learning process through a variety of activities that stimulate critical thinking, reflection, and interaction between students and the learning material. This article discusses the basic concepts of active learning and highlights some strategies that can be applied in PAI learning. Active learning strategy is an educational approach that aims to improve the quality of education and requires various supporters in the teaching and learning process to achieve effective and efficient student engagement. By implementing active learning strategies, teachers want students to participate in the learning process mentally and physically, so that the learning atmosphere becomes pleasant and students do not get bored.